PRODUK MAKANAN TIDAK SESUAI SPESIFIKASI BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Yamin, Saefullah; Arta Uli Sihaloho, Sari (Universitas Wiralodra, 2021)
Consumer Protection is a form of legal protection given to consumers in their efforts to meet their needs from things that can harm the consumers themselves. Therefore, talking about consumer protection means questioning guarantees or assurances about the fulfillment of consumer rights. In the legal field, this term is still relatively new, especially in Indonesia, while in developed countries consumer protection is discussed along with the development of industry and technology. In this study formulate the problem of how the legal protection of consumers for defective food products and how the responsibility of business actors for defective food products. The research method used is a normative juridical approach with data collection techniques through library research, both primary legal materials, namely reference books and regulations related to consumer protection, secondary legal materials, and tertiary legal regulations. The purpose of this study is to find out how the legal protection of consumers for defective food products and describe how the responsibility of business actors for defective food products. The theory used in this study uses the rule of law theory and the theory of legal protection. In this study, it can be concluded that consumers' rights are protected against products that are not in accordance with what they should be. In the case of sausages containing maggots, it is hoped that business actors or PT. So Good Food compensates for losses and improves quality control in producing its products.